2006
DOI: 10.1111/j.1365-246x.2005.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress interaction between seismic and volcanic activity at Mt Etna

Abstract: International audienceMt Etna lies on the footwall of a large normal fault system, which cuts the eastern coast of Sicily and crosses the volcano eastern flank. These faults are responsible for both large magnitude historical earthquakes and smaller damaging seismic events, closer to the volcano. We investigate here the two-way mechanical coupling between such normal faults and Mt Etna through elastic stress transfer. The comparison between eruptive sequences and historical seismicity reveals that the large ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…Thus, the magma chamber did not significantly contribute to the observed surface deformation during the period of this study. Assuming the absence of major activity in the magma chamber, it was proposed that minor coulomb stress changes of the deep magma chamber induced the clamping and unclamping of fault planes as shown in the case studies by [79,82]. It is characterized by predominantly normal faulting in the focal mechanisms of the 2007 observation towards a tendency of strike-slip faulting in the 2008 observation.…”
Section: Interpretation Of Stamps/mti Processing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the magma chamber did not significantly contribute to the observed surface deformation during the period of this study. Assuming the absence of major activity in the magma chamber, it was proposed that minor coulomb stress changes of the deep magma chamber induced the clamping and unclamping of fault planes as shown in the case studies by [79,82]. It is characterized by predominantly normal faulting in the focal mechanisms of the 2007 observation towards a tendency of strike-slip faulting in the 2008 observation.…”
Section: Interpretation Of Stamps/mti Processing Resultsmentioning
confidence: 99%
“…Since only a few StaMPS/MTI results showed clear surface deformation and produced the source parameters in reasonable ranges, we In the first scenario, a Mogi-type magma chamber of spherical shape in an elastic half-space [70] and four faults lines inferred from [5] were introduced. In this scenario the central magma chamber contributes to surface unrest by volume or pressure changes interacting with the faults lines as shown by, e.g., Feuillet et al [79]. Figure 12 and Table 3 present the observed and modelled Both models were optimized using the Levenberg-Marquardt algorithm (LMA) which was implemented using Gauss-Newton iteration and loops in order to obtain a convergence of the gradient descent [75].…”
Section: Interpretation Of Stamps/mti Processing Resultsmentioning
confidence: 99%
“…Static stress also plays a significant role in near-field interactions between tectonic earthquakes and volcanic eruptions (e.g. Feuillet et al, 2006;Walter and Amelung, 2006;Walter, 2007;Walter and Amelung, 2007).…”
Section: Volcanoesmentioning
confidence: 99%
“…On the basis of the morphometric features of flank cones and their feeding structures, Villari et al (1988) interpreted the development of the eruptive fractures in the medium and upper flanks of the volcano as caused by overpressure of the magmatic column within the central conduit. In this regard, Feulliet et al (2006) also showed that large shallow reservoirs preferentially lead to central or lateral eruptions (connected to the central system) on the medium and upper volcano flanks more than "eccentric" eruptions (flank eruptions not connected to the central system; cf. Rittmann 1973).…”
Section: Plumbing System Geometrymentioning
confidence: 95%
“…This may prevent the vertical propagation of dykes from depth and promote magma storage in shallow sill-like reservoirs under compression (cf. Feulliet et al 2006).…”
Section: Plumbing System Geometrymentioning
confidence: 95%